MSMEs in Times of Crisis. Evidence from Indonesia - Tambunan, Tulus (Journal of Developing Economies, 2020)
This descriptive study is about micro, small and medium enterprises (MSMEs) in Indonesia. It has two objectives: (i) to estimate the impact of the Covid 19 crisis on MSMEs and compares it with other previous problems. Second, to explore crisis mitigation (CM) measures adopted by affected MSMEs. It shows that different types of crises have different transmission channels through which such situations affected MSMEs. CM measures adopted by affected MSMEs also vary by different types of emergencies and hence various business risks. In the 1997/98 crisis, replacing imported raw materials with local raw materials was widely adopted. The 2008/09 problem was finding new customers or markets in unaffected countries or switching to the domestic market. While in the case of the Covid-19 crisis, switching temporarily to manufacturing medical devices such as masks and changing the marketing system from conventional to e-commerce are the most widely adopted strategies. There is already a lot of literature on economic crises such as the 1997/98 Asian financial crisis and the 2008 global economic crisis. The Covid 19 pandemic's reports and articles impact on the economy have emerged in the past two months. To the best of the author's knowledge, this is the first study on how such crises affected and through what transmission channels, MSMEs.  Keywords: MSMEs, 1997/98 Asian Financial Crisis, 2008/09 Global Financial Crisis, COVID-19 Crisis, CM Measures JEL: D2, F6, G01, I1